THE EFFECTIVENESS OF TASK COORDINATION SYSTEM IN KOTARAJA VILLAGE GOVERNMENT, DULUPI DISTRICT - Rika Rauf; Ikram Muhammad; Fibriyanti s. Lakoro (Journal of Economic, Business, and Administration (JEBA), 2024)
The research objective was to determine the effectiveness of the task coordination system in the Kotaraja Village Government. As well as to determine the effectiveness of the task coordination system vertically and horizontally in the Kotaraja Village Government. The research approach used in this research is a qualitative approach and a descriptive research type. The informants in this study were village secretaries, 6 village officials and 1 person from BPD. Data collection techniques used in this study were observation, in-depth interviews and documentation. The data analysis technique used was data analysis technique by processing the data using the Miles and Huberman Models. The results of the study are 1) The vertical coordination system that was built between the village head and village officials has not gone well, due to a lot of pressure and various conditions that are not in accordance with village development plans so that the community gives an unfavorable impression. 2) The horizontal coordination system that was built between the Village Head and the Kotaraja Village BPD has not worked properly in carrying out task coordination but has not been effective, because the BPD sometimes does not receive clear information regarding the Kotaraja village development planning.